2018
DOI: 10.7150/thno.24385
|View full text |Cite
|
Sign up to set email alerts
|

α-Viniferin Improves Facial Hyperpigmentation via Accelerating Feedback Termination of cAMP/PKA-Signaled Phosphorylation Circuit in Facultative Melanogenesis

Abstract: Rationale: cAMP up-regulates microphthalmia-associated transcription factor subtype M (MITF-M) and tyrosinase (Tyro) in the generation of heavily pigmented melanosomes. Here, we communicate a therapeutic mechanism of hyperpigmented disorder by α-viniferin, an active constituent of Caragana sinica.Methods: We used cAMP-elevated melanocyte cultures or facial hyperpigmented patches for pigmentation assays, and applied immunoprecipitation, immunobloting, RT-PCR or reporter gene for elucidation of the antimelanogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Because CREB is believed to play a major role in conveying UVR-stimulated a-MSH signals to induce MITF expression and downstream melanogenic genes, we reasoned that the molecules that suppress the transcriptional activity of CREB could be potential therapeutic candidates for hyperpigmentation disorders. Supporting our presumption, recent works from Yun et al (2018) have demonstrated that inhibition of the protein kinase A/CREB/CRTC pathway using a-viniferin successfully improves hyperpigmentation by reducing MITF.…”
Section: Discussionsupporting
confidence: 59%
“…Because CREB is believed to play a major role in conveying UVR-stimulated a-MSH signals to induce MITF expression and downstream melanogenic genes, we reasoned that the molecules that suppress the transcriptional activity of CREB could be potential therapeutic candidates for hyperpigmentation disorders. Supporting our presumption, recent works from Yun et al (2018) have demonstrated that inhibition of the protein kinase A/CREB/CRTC pathway using a-viniferin successfully improves hyperpigmentation by reducing MITF.…”
Section: Discussionsupporting
confidence: 59%
“…The IC 50 of gnetin C activity against tyrosinase and melanin biosynthesis was 7.0 and 7.6 mM respectively, whereas resveratrol exerted IC 50 of 7.2 and 7.3 mM respectively. The anti-melanogenesis response of resveratrol trimer, a-viniferin which is present in melanocytes and human skin was evaluated in a study conducted by Yun et al [146].…”
Section: Hyperpigmentationmentioning
confidence: 99%
“…Nuclear-cytoplasmic shuttling of CRTC1 is regulated by its phosphorylation status 19. Inhibition of PP2B or PKA restores p-CRTC1 levels in α-MSH- or db-cAMP-activated B16-F0 cells, whereas the inhibition of PP1, PP2A or p38 MAPK has no effects, even though all of them decrease melanin production 31. We further examined which phosphatase or kinase pathway could switch the translocation of CRTC1 in α-MSH-, ET-1- and WH-4-023-activated cells.…”
Section: Resultsmentioning
confidence: 99%